2002
DOI: 10.1095/biolreprod67.1.80
|View full text |Cite
|
Sign up to set email alerts
|

An Environmentally Relevant Organochlorine Mixture Impairs Sperm Function and Embryo Development in the Porcine Model1

Abstract: We evaluated the effects of an environmentally relevant mixture of more than 15 organochlorines on the development of pig oocytes and sperm during in vitro fertilization (IVF). Oocytes were cocultured with sperm in IVF medium containing increasing concentrations of an organochlorine mixture, similar to that found in women of highly exposed populations. Exposure to the organochlorine mixture diminished oocyte penetration rates and polyspermy in a linear manner. The mixture did not affect rates of cleavage nor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 51 publications
(73 reference statements)
2
18
0
7
Order By: Relevance
“…Similar effects were observed when pig spermatozoa were cultured in IVF medium containing a mixture of 15 organochlorines (Campagna et al 2002).…”
Section: Effects Of Edcs On Testicular Functionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar effects were observed when pig spermatozoa were cultured in IVF medium containing a mixture of 15 organochlorines (Campagna et al 2002).…”
Section: Effects Of Edcs On Testicular Functionsupporting
confidence: 67%
“…Although there was no effect on the number of cleaved oocytes, the number of zygotes that became blastocysts was substantially reduced (Brevini et al 2004;Favetta et al 2012). Further exposure of porcine oocytes and/ or embryos to OP or organochlorines (OCs) variously altered oocyte viability, fertilisation rate and morula development (Campagna et al 2002(Campagna et al , 2008Ducolomb et al 2009). …”
Section: Developmental Programming In Farm Animalsmentioning
confidence: 99%
“…This result agrees with a study by Betancourt et al, 21 who found that these 2 herbicides affect sperm mobility and that after 1 hour of incubation with 50 mM FE or atrazine, sperm viability decreases to 13% and 24%, respectively. All these results are in close agreement with those reported previously by Campagna et al, 38 who found that sperm motility is immediately reduced in a dose-dependent manner by organochlorine treatment. The reduction in sperm quality could account for the decrease in fertilization.…”
Section: Discussionsupporting
confidence: 93%
“…Supporting these findings, non-genomic studies have shown a decrease in motility (Table 1) after exposure to low levels of 2,2 0 ,6,6 0 tetrachlorobiphenyl (PCB54; Roediger et al 1989) and 2,4,4 0 -trichlorobiphenyl (PCB28), 2,4,6-trichlorobiphenyl (PCB30), and 2,3 0 ,4,4 0 ,5-pentachlorobiphenyl (PCB118; Yurdakok et al 2015) in human and bull spermatozoa. Moreover, porcine sperm treated with an organochlorine mixture containing several PCB congeners plus a panoply of other compounds, including pesticides, were also found to reduce both motility and viability in vitro (Campagna et al 2002). In sharp contrast, exposure to reasonably high concentrations (2-20 mg/ml) of the non-dioxin-like 2,2 0 ,4,4 0 ,5,5 0 -hexachlorobiphenyl (PCB153) and dioxinlike PCB congeners 118, 126 (3,3 0 ,4,4 0 ,5-pentachlorobiphenyl) and 77 (3,3 0 ,4,4 0 -tetrachlorobiphenyl) failed to produce any effect on human sperm movement, viability and spontaneous acrosome reaction after 5 h of incubation (Pflieger-Bruss et al 2006a,b).…”
Section: Polychlorinated Biphenylsmentioning
confidence: 99%